ADA: an open-source software platform for plotting and analysis of data from laboratory photobioreactors. Issue 1 (31st December 2022) - Mapstone, Lydia J.; Taunt, Henry N.; Cui, Jing; Purton, Saul; Brooks, Tom G. R.
ABSTRACT: Algal biotechnology has received significant attention over the past two decades in fields ranging from biofuels to cosmeceuticals. However, the development of domesticated or genetically engineered microalgal strains for commercial applications depends on accurate and reliable growth data. To this end, several companies have developed lab-scale photobioreactors (PBRs) that enable precision control of conditions and automated growth recording. Whilst the transition from manual control of conditions and measurements to automated systems has allowed researchers to greatly improve the accuracy and scope of cultivation experiments, it has also presented novel challenges. The most pertinent of these being the analysis of the copious quantities of data produced. A standard PBR experiment can contain tens or even hundreds of thousands of data points, and often features outliers, noise, and a requirement for datasets to be calibrated with a standard curve or merged with replicates. Furthermore, complex analysis of multiple curves may be required in order to extract information such as the gradient or fit to a growth model. This can be laborious, time consuming and is not standardized between research groups. Proprietary software provided with most PBRs tends to lack these more advanced features and is typically unable to process data from other PBR manufacturers. To address these issues, we have developed the Algal Data Analyser (ADA), an open-source software platform providing the tools to rapidly plot and analyse microalgal data. ADA can simultaneously interpret datasets from three major PBR suppliers (Algenuity, Industrial Plankton, Photon Systems Instruments), and can also incorporate data from manual readings. Users can rapidly produce standardized, publication ready plots, and analyse multiple growth curves in parallel. Future iterations of ADA will include compatibility with datasets from other PBR suppliers as they become available, with the aim of making it a universal platform for all PBR data.